Total colonic aganglionosis: multicentre study of surgical treatment and patient-reported outcomes up to adulthood. Issue 5 (13th July 2020) - Stenström, P; Kyrklund, K; Bräutigam, M; Engstrand Lilja, H; Juul Stensrud, K; Löf Granström, A; Qvist, N; Söndergaard Johansson, L; Arnbjörnsson, E; Borg, H; Wester, T; Björnland, K; et al.
Abstract: Background: Surgery for total colonic aganglionosis (TCA) is designed to preserve continence and achieve satisfactory quality of life. This study evaluated a comprehensive group of clinical and social outcomes. Methods: An international multicentre study from eight Nordic hospitals involving examination of case records and a patient-reported questionnaire survey of all patients born with TCA between 1987 and 2006 was undertaken. Results: Of a total of 116 patients, five (4·3 per cent) had died and 102 were traced. Over a median follow-up of 12 (range 0·3–33) years, bowel continuity was established in 75 (73·5 per cent) at a median age of 11 (0·5–156) months. Mucosectomy with a short muscular cuff and straight ileoanal anastomosis (SIAA) (29 patients) or with a J pouch (JIAA) (26) were the most common reconstructions (55 of 72, 76 per cent). Major early postoperative complications requiring surgical intervention were observed in four (6 per cent) of the 72 patients. In 57 children aged over 4 years, long-term functional bowel symptoms after reconstruction included difficulties in holding back defaecation in 22 (39 per cent), more than one faecal accident per week in nine (16 per cent), increased frequency of defaecation in 51 (89 per cent), and social restrictions due to bowel symptoms in 35 (61 per cent). Enterocolitis occurred in 35 (47 per cent) of 72 patients. Supplementary enteral and/or parenteral nutrition was required by 51 (55 per cent) of 93 patients at any time during follow-up. Of 56 responders aged 2–20 years, true low BMI for age was found in 20 (36 per cent) and 13 (23 per cent) were short for age. Conclusion: Reconstruction for TCA was associated with persistent bowel symptoms, and enterocolitis remained common. Multidisciplinary follow-up, including continuity of care in adulthood, might improve care standards in patients with TCA. Graphical Abstract: In a multicentre study, outcome of surgery for total colonic aganglionosis was evaluated in 116 patients. In long-term follow-up, patients with a J pouch reconstruction reported better faecal continence and those with a Duhamel reconstruction reported fewer episodes of enterocolitis. Nutritional support was needed extensively in all groups with various lengths of resected aganglionotic bowel. Problems persist into adulthood